# Class 11 NCERT Solutions- Chapter 5 Complex Numbers And Quadratic Equations – Exercise 5.2

• Last Updated : 25 Jan, 2021

### Question 1.  z = – 1 – i √3

Solution:

We have,

Hey! Looking for some great resources suitable for young ones? You've come to the right place. Check out our self-paced courses designed for students of grades I-XII

Start with topics like Python, HTML, ML, and learn to make some games and apps all with the help of our expertly designed content! So students worry no more, because GeeksforGeeks School is now here!

z = -1 – i√3

We know that, z = r (cosθ + i sinθ)

Therefore,

r cosθ = -1  —(1)

r sinθ = -√3  —-(2)

On Squaring and adding (1) and (2), we obtain

r2 (cos 2θ + sin 2θ) = (-1)2 + (-√3)2

r2 = 1 + 3

r = √4

Since r has to positive, Therefore r = 2

Putting r = 2 on (1) and (2), we get

cosθ = -1 / 2 and sinθ = -√3 / 2

Therefore, θ = – 2π / 3 (Since cosθ and sinθ both are negative, therefore θ lies in third quadrant)

Hence, modulus and argument of z = -1 – i√3 are 2 and – 2π / 3 respectively.

### Question 2. z =  -√3 + i

Solution:

We have,

z = -√3 + i

We know that, z = r (cosθ + i sinθ)

Therefore,

r cosθ = -√3  —(1)

r sinθ = 1  —-(2)

On Squaring and adding (1) and (2), we obtain

r2 (cos 2θ + sin 2θ) = (-√3)2 + (1)

r2  = 3 + 1   (Since, cos 2θ + sin 2θ = 1)

r2 = 3 + 1

r = √4

Since r has to positive, Therefore r = 2

Putting r = 2 on (1) and (2), we get

cosθ = -√3 / 2 and sinθ = 1 / 2

Therefore, θ = 5π / 6 (Since cosθ negative and sinθ positive, therefore θ lies on second quadrant)

Hence, modulus and argument of z = -√3 + i are 2 and 5π / 6 respectively.

### Question 3. 1 – i

Solution:

We have z = 1 – i,

Let  r cosθ  = 1   —(1)  and,

r sinθ  = -1 —(2)

On Squaring and adding  (1) and (2) , we obtain

r2 (  cos 2θ + sin 2θ  )  =  (1)2 + (-1)

r2 =  2

r = √2 ( Since r has to be positive )

Putting r = √2 on (1) and (2) , we get

cosθ = 1 / √2  and  sinθ = -1 / √2

Therefore, θ =  – π / 4 ( Since cosθ positive and sinθ  negative, therefore θ is negative as it lies on fourth quadrant)

Hence , z in polar form:  z =  r cosθ  + i  r sinθ = √2 (cos (- π / 4) + i sin (- π / 4)).

### Question 4. -1 + i

Solution:

We have z = -1 + i,

Let  r cosθ  = -1   —(1)  and,

r sinθ  = 1 —(2)

On Squaring and adding (1) and (2), we obtain

r2 (cos 2θ + sin 2θ)  = (-1)2 + (1)2

r2 = 2

r = √2 (Since r has to be positive)

Putting r = √2 on (1) and (2), we get

cosθ = -1 / √2 and sinθ = 1 / √2

Therefore, θ = 3π / 4 (Since cosθ negative and sinθ positive, therefore θ is positive as it lies on second quadrant)

Hence, z in polar form:  z = r cosθ + i  r sinθ = √2 (cos (3π / 4) + i sin (3π / 4)).

### Question 5. -1 – i

Solution:

We have z = -1 – i,

Let  r cosθ  = -1   —(1)  and,

r sinθ  = -1 —(2)

On Squaring and adding  (1) and (2), we obtain

r2 (cos 2θ + sin 2θ)  =  (-1)2 + (-1)2

r2 =  2

r = √2 ( Since r has to be positive )

Putting r = √2 on (1) and (2) , we get

cosθ = -1 / √2  and  sinθ = -1 / √2

Therefore,  θ =  -3π / 4 (Since  cosθ  negative and sinθ  negative, therefore θ is negative as it lies on third quadrant)

Hence, z in polar form:  z =  r cosθ  + i  r sinθ  = √2 (cos (-3π / 4) + i sin (-3π / 4)).

### Question 6.  -3

Solution:

We have z = -3,

Let  r cosθ  = -3   —(1)  and,

r sinθ  = 0 —(2)

On Squaring and adding (1) and (2), we obtain

r2 (cos 2θ + sin 2θ) =  (-3)2 + (0)

r2 = 9

r = 3 (Since r has to be positive)

Putting r = 3 on (1) and (2), we get

cosθ = -3 / 3  and  sinθ = 0 / 3

Therefore,  θ =  π

Hence, z in polar form:  z =  r cosθ  + i  r sinθ = 3(cos (π) + i sin (π)).

### Question 7. √3 + i

Solution:

We have z = √3 + i,

Let  r cosθ  = √3  —(1)  and,

r sinθ  = 1 —(2)

On Squaring and adding  (1) and (2) , we obtain

r2 (cos 2θ + sin 2θ) = (√3)2 + (1)2

r2 = 4

r = 2 (Since r has to be positive )

Putting r = 2 on (1) and (2), we get

cosθ = √3 / 2 and  sinθ = 1 / 2

Therefore, θ =  π / 6 ( Since  cosθ  positive and sinθ  positive, therefore θ is positive as it lies on first quadrant)

Hence, z in polar form:  z =  r cosθ  + i  r sinθ  = 2 (cos (π / 6) + i sin (π / 6)).

### Question 8. i

Solution:

We have z = i,

Let  r cosθ  = 0 —(1)  and,

r sinθ  = 1 —(2)

On Squaring and adding  (1) and (2) , we obtain

r2 (cos 2θ + sin 2θ)  =  (0)2 + (1)

r2 =  1

r = 1 (Since r has to be positive)

Putting r = 1 on (1) and (2), we get

cosθ = 0 / 1 and sinθ = 1 / 1

Therefore, θ = π / 2

Hence, z in polar form: z = r cosθ + i r sinθ = cos (π / 2) + i sin (π / 2)

My Personal Notes arrow_drop_up